Rehabilitation Medicine - Kim, Chong-Tae (IntechOpen, 2012)
Rehabilitation medicine is a medical specialty with a focus on functional improvement and quality of life. Professionals working in rehabilitation medicine care about not only medical but also functional problems. There have been significant changes in rehabilitation medicine with development of basic science and computer technology in the last several decades. Collaboration with other areas of science and engineering has contributed to improvements in rehabilitation outcomes. Also, changes in the medical delivery system has resulted in increasing necessity of rehabilitation. Like most articles published by InTech, those in this text are intended to review current practical guidelines and to introduce updated knowledge and skills. I hope that the readers will appreciate the useful information provided within this text.